Resilience and sport - Monteiro, Luciana Bernardes Vieira de Rezende Hersen; Silva , Carlos Alberto Figueiredo da; Osborne , Renata; Araújo , Carla Isabel Paula da Rocha (Seven Editora, 2023)
This research aims to investigate in the literature the contributions of sports social projects (PSE) and their connection with the development of the student’s body image and the promotion of resilience through sport. This article is a narrative review of the literature, where a path was sought to present studies of PSE strands, collecting, especially, the texts that addressed resilience. For being a current theme, the PSE still has scarce literature. Resilience is also a new topic that needs further study. The issue of resilience in PSE is even lower, with a large gap to be filled. The findings show to a large extent that PSEs provide benefits thanks to the regular practice of sports and collaboration in the moral formation of their students. However, there is also a “shadow side of the sport”, showing that many of the PSEs are palliative, as they have shallow goals and no clear goals. For a better analysis of the contribution of PSE and the development of resilience, more studies are needed that relate to these themes because the material found is still tiny. Even so, this article presents the most used concepts related to these themes, trying to contribute to a more significant discussion. Many youths assisted by the PSE are socially vulnerable subjects who daily suffer traumas linked to their social and cultural conditions. However, they can get out of the immobilization caused by these traumas and overcome these adversities by re-signifying their image body. Hence, there is a need for a reaction potential, a process known as resilience. Thus, PSEs can be an essential tool in promoting their students’ resilience, as they are a foundation for overcoming adversities. DOI:https://doi.org/ 10.56238/devopinterscie-135